Management of Healthcare Service Sector—A Study of Primary Health Centres - Singh, R.; Sunaina, (Indian Journal of Marketing, 2005)
Health is considered as the most important thing for a human being. It is a well known concept that health is wealth. That is why the Government of India emphasizes on health and protects the poor people from sickness .There is a provision of establishing primary health centers in villages to meet the health needs and demands of the individual and the community. The programme of establishing primary health centre in each Community Development Block, having a population of 60,000 to 80,000 was launched on October 2, 1952 as an integrated part of the Community Development Programme.At present there are 23,000 primary health centers and 1,37,000 sub-centers in the country. Primary health centers are institutions providing comprehensive (i.e. preventive, promotive and curative) health care services to the people living in a defined geographic area. It seeks to achieve its purpose by grouping under one roof of coordinates in some other manner all the health work of that area. Health planners in India have visualized the primary health centre as the minimum infrastructure for the delivery of health care services to the people in rural areas. It is the first contact point between village community and medical officer. These are established and maintained by the state Governments under the Minimum Needs Programme(MNP)/Basic Minimum Services Programme.It is manned by a medical officer supported by paramedical and other staff and provides beds to patients and acts as a referral unit for sub centres.The Tenth Five Year plan of the Government of Punjab has emphasized on mental health care, proper disposal of biomedical waste, setting up of Para medical services, opening up of new dispensaries in slum area, provision of toilets and attendants, establishment of new primary health centers up gradation of existing sub-health centre to primary health centers.